A geometric model for the periodic undulation of a confined adhesive crack. Issue 6 (24th December 2015) - Wei, Zhiyan; Mahadevan, L.
Abstract : Inspired by experiments on the instability of confined interfacial cracks, we construct a minimal mathematical model based on symmetry arguments that can reproduce the form of the crack front in a confined domain. Image adapted fromref. 29 . Abstract : Inspired by experiments on the instability of confined interfacial cracks, we construct a minimal mathematical model based on symmetry arguments that can reproduce the form of the crack front in a confined domain. We show that the model can be interpreted in terms of the buckling and post-buckling response of a compressed elastica with a nonuniform bending stiffness that is adhered to a linearly elastic substrate. The model has three parameters that allow us to capture the primary wavelength associated with the onset of an undulatory instability of a straight crack front, as well as the finger amplitudes and finger widths in the nonlinear development of the instability. We determine these parameters using an optimization procedure that minimizes the square error between the computed profile and experimental observations. The results of this procedure yield numerical solutions that agree well with the finger profiles experimentally observed in films of different thicknesses. Our approach shows the efficacy of simple models based on symmetry in explaining interfacial instabilities governed by different physical mechanisms.